PABRIK FENOL DARI CUMEN Kapasitas 200.000 Ton/Tahun - , FIANNY KARTIKA PUSPA, Budhijanto, S.T., M.T., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The process used in this plant is Cumene Process, namely by reacting cumeen (main raw material) obtained by imports from Thailand as 39248.6812 kg / h and oxygen from the air as much 16384.7150 kg / h at a flow stirred tank reactors with bubbling process which produces cumen hydroperoxide. Cumen hydroperoxide decomposed using sulfuric acid catalyst (adjuvant) as much as 19.4637 kg / h in flow stirred tank reactor as the reaction runs optimally at acidic conditions. After obtaining phenol (primary products) as much 26010.1010 kg / h and acetone (product side) as much 16048.7857 kg / hour of cracking the cumen hydroperoxide, solution is then reacted with a mixture of sodium hydroxide (adjuvant) of 0.9535 kg / hours to neutralize the acidic solution. This phenol plant is planned to be located in Cilegon and occupies a land area of 4 ha. Cilegon has the basics of considerations in the selection of the plant site infrastructures adequate transportation facilities, land and water needs are available, availability of labor, geographical and climatic conditions are stable. In the design of cumen phenol plant with a capacity of 200,000 tonnes / year requires a total energy requirement of 62,498,508.23 kj / hour. This plant needs water at 760,258.0102 tons / year. Calculation of economic evaluations obtained a fixed capital of U.S. $ 13,696,707.22 + USD. 10,239,882,859.10 working capital of U.S. $ 20,683,227.13 + USD. 1,469,652,694.80, yielding cost of U.S. $ 74,579,253.27 + USD. 8,570,012,955.04. Public expenditure of U.S. $ 6,437,174.50 + Rp. 1,191,713,807.19. Profit before tax of Rp. 37,290,421,358.62 profit after tax of Rp. 18,645,210,697.31. ROI before taxes 26.31%, 13.16% ROI after tax. POT before tax of 2.75 years, 4.32 years after tax POT. BEP capacity by 51.41%, SDP 28.62% of capacity, and DCFRR of 24.87%. Based on the economic calculations, this phenol plant from cumene with a capacity of 200,000 tonnes / year interesting for further investigation.